Modern Yaşamın Göstergelerinden Yüksek Binalarda Renk - Işık Faktörü Bağlamında “Hasta Bina Sendromu” Ve İletişimsel Boyutta Etkileri - Zeybek, Işıl (The Turkish Online Journal of Design Art and Communication, 2014)
The enormous high-rises, plazas, residences and towers that have encapsulated urban living space, are smart structures that are constructed for either personal, social or for business purposes. If we are to assume that more than half of one’s daily practices, movements and routines take place within enclosed walls, then it is safe to say that these spaces have a significant role in the social process. These spaces, which are designed to facilitate the high pace and high speed of one’s daily life, also appear before us as structures that threaten our health and productivity. In other words, they affect effective and efficient interaction amongst human beings negatively and cause communication conflicts due to their unfavorable impact on a psychological and psycho-neurological level. Hence, these impressive, grandiose and imposing buildings are, in fact, damaging and unhealthy lifestyle indicators; a kind of ‘sickness’ which scientists active in different fields have been discussing. This ‘sickness’ has been named “Sick Building Syndrome”, or “Middle Class Sickness”. In the study that follows, examples will be given and analyzed from a semiolotical perspective to show how the use of color and light can make a difference for people living and working in high-rise buildings to physically and psychologically feel better, have a more positive way of thinking, restore their inner peace and interpersonal relationships and become healthier beings.
Keywords: Hasta Bina Sendromu; Göstergebilim; Renk; Işıklandırma; Psikolojik Etki; Yüksek Katlı Binalar; Gösterge; Sick building syndrome; Semiotics; Colors; Lighting; Pyschological Impact; High Rise Building; Signs